The male‐produced aggregation pheromone of the bean flower thrips Megalurothrips usitatus in China: identification and attraction of conspecifics in the laboratory and field. Issue 9 (21st April 2020) - Liu, Pingping; Qin, Zifang; Feng, Mingyue; Zhang, Liu; Huang, Xinzheng; Shi, Wangpeng
Abstract: BACKGROUND: Thrips, Megalurothrips usitatus, usually display aggregation behavior, which is probably mediated by a male‐produced aggregation pheromone. Aggregation pheromones are species‐specific, and can be used to develop commercial lures for monitoring and mass‐trapping of pests. The active components of the aggregation pheromone for four thrips species have been identified. However, the components of M. usitatus‐ produced aggregation pheromone are still not clear. RESULT: Y‐tube olfactometer assays showed that both male and virgin female M. usitatus were significantly attracted to male but not female volatiles. This was additionally supported by electroantennogram (EAG) assays. Coupled gas chromatography‐electroantennogram detection (GC‐EAD) showed that one component of male‐specific odors elicited a significant electrophysiological response. This compound was characterized as (2 E, 6 E )‐farnesyl acetate, which is structurally different from the active components of the aggregation pheromones of other reported thrips species. Electroantennal responses of M. usitatus increased with increasing doses of synthetic (2 E, 6 E )‐farnesyl acetate. Additionally, this compound significantly attracted adults in laboratory behavioral bioassays. Under field conditions, sticky traps with synthetic (2 E, 6 E )‐farnesyl acetate caught 1.5‐7‐fold more M. usitatus than controls, and this effect of the compound at a dose of 60 μg lasted at least 6 days. CONCLUSION: (2 E, 6 E )‐Farnesyl acetate was identified as the male‐produced aggregation pheromone of M. usitatus . It could attract this thrips species under laboratory and field conditions, suggesting considerable potential as a commercial application to control M. usitatus populations. © 2020 Society of Chemical Industry Abstract : The (2 E, 6 E )‐farnesyl acetate was identified as the male‐produced aggregation pheromone of the Megalurothrips usitatus and attract conspecifics under both laboratory and field conditions.